Pengaruh Iklan Online dan Harga terhadap Keputusan Pembelian dengan Minat Beli sebagai Variabel Intervening pada Konsumen Tokopedia di Kota Makassar - Hamka, Wahyuni; Effendi, Ahmad; Jafar, Akhmad (Study of Scientific and Behavioral Management, 2023)
ABSTRACT The purpose of this study is: First, to analyze the influence of online advertising on purchasing decisions. Second, to analyze the effect of price on purchasing decisions. Third, to analyze the effect of online advertising on buying interest. Fourth, to analyze the effect of price on buying interest. Fifth, to analyze the influence of buying interest on purchasing decisions. Sixth, to analyze the influence of online advertising on purchase decisions through buying interest as an intervening variable. Seventh, to analyze the effect of price on purchasing decisions through buying interest as an intervening variable. The sampling technique used was non-probability with a sample of 105 respondents. The data analysis technique in this study is using Structural Equation Modeling (SEM) using the help of smartPLS version 3.0 for windows. The results of this study show that: First, online advertising has a positive and significant effect on purchasing decisions. Second, price has a negative and insignificant effect on purchasing decisions. Third, online advertising has a positive and significant effect on buying interest. Fourth, prices have a positive and significant effect on buying interest. Fifth, buying interest has a positive and significant effect on purchasing decisions. Sixth, online advertising has a positive and significant effect on purchasing decisions through purchase interest as an intervening variable. Seventh, price has a positive and significant effect on purchasing decisions through buying interest as an intervening variable. Keywords: Online Advertising, Price, Purchase Decision, Buying Interest